Natural History and Factors Associated with Early and Delayed Mortality in HIV-Infected Patients Treated of Tuberculosis under Directly Observed Treatment Short-Course Strategy: A Prospective Cohort Study in India - Alvarez-Uria, Gerardo; Naik, Praveen Kumar; Pakam, Raghavakalyan; Bachu, Lakshminaryana; Midde, Manoranjan (Interdisciplinary Perspectives on Infectious Diseases, 2012)
Despite the impressive global results of DOTS in India, the effectiveness of DOTS for the treatment of tuberculosis in HIV-infected patients is not well known. This is an observational prospective cohort study performed in Anantapur District, Andhra Pradesh, India. The study included 1000 DOTS antituberculosis treatment (ATT) episodes and 840 person-years. CD4 lymphocyte count was below 200 cells/mm3 in 77% of the cases, and 21% were retreatments. Two thirds were presented with extrapulmonary tuberculosis, and the most common form of extrapulmonary tuberculosis was tuberculous meningitis followed by pleuritis, abdominal tuberculosis, and lymphadenitis. Cumulative incidence of mortality was 16%, 26%, 39%, and 46% at 1, 3, 12, and 24 months, respectively. Factors associated with three-month (early) mortality were being homeless, having low CD4+ lymphocyte count, having tuberculous meningitis, belonging to a socially disadvantaged community, having more than 35 years, and being on an antiretroviral therapy at the moment of initiating the ATT. Factors associated with delayed mortality were having low CD4+ lymphocyte count, belonging to a socially disadvantaged community, receiving a category II ATT because of a previous episode of ATT and having acid fast bacilli in sputum before the ATT initiation. These findings indicate that there is an urgent need to improve the treatment of tuberculosis in HIV-infected patients in India.